Internasionalisasi dan Digitalisasi Branding Ecovillage Malagufuk Berbasis Sustainable Tourism - Agus Setiawan; Endra Putra Raharja; Jusmin; Mersi Axelina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
Malagufuk Village is known for its potential as a conservation-based birdwatching ecotourism village in natural forests. Through its ecotourism potential, Malagufuk Village is increasingly visited by foreign tourists. Even though the graph shows an increase, researchers found various obstacles based on observations in the field. One of the problems experienced by local tour guides from Malagufuk Village is their low English language skills. This lack of English language skills has limited the ability of tour guides to provide information. tour guide, explaining the uniqueness and ecotourism potential of Malagufuk Village, as well as facilitating smooth interaction between tourists and local residents. The aim of this activity is to improve community welfare and independence through empowerment in the tourism sector. The methods in this activity consist of socialization, training, application of technology, mentoring and evaluation, as well as a desire program. The result of this activity is that the tour guide has weaknesses in speaking good English, then there is no optimization of digital branding. All obstacles found can be overcome with the solutions offered. All the people of Malagufuk Village, especially the administrators and tour guides, can speak English well and are able to carry out digital marketing effectively.